Multidisciplinary Surveys: a contractors 10 tips. - Stubbing, D.; Smith, K.; Cox, S. (The International Hydrographic Review, 2019)
Discovery Marine Ltd (DML) is a Small to Medium Enterprise (SME) in the hydrographic industry and has been providing contract services to Land Information New Zealand (LINZ), New Zealand’s Hydrographic Authority (NZHA) for the last 10 years. The procurement model and service delivery approaches have altered during this tenure, realizing tangible benefits to both government and industry.